Overview of the Nontyphoidal and Paratyphoidal Salmonella Vaccine Pipeline: Current Status and Future Prospects. (29th July 2020) - Baliban, Scott M; Lu, Ying-Jie; Malley, Richard
Abstract: Nontyphoidal Salmonella and Salmonella Paratyphi are responsible for significant morbidity and mortality worldwide. To date, no vaccine has been licensed against these organisms. The development of effective vaccines remains an urgent priority. In this review, the rationale for and current status of various vaccine candidates against S . Paratyphi and nontyphoidal Salmonella are presented, with a focus on the research findings from the 2019 International Conference on Typhoid and Other Invasive Salmonelloses. Additionally, other vaccine candidates that are currently undergoing clinical development are highlighted. Future approaches, which may include antigens that are genetically conserved across Salmonella and confer broad, non–serotype-specific protection, are also discussed.